2015
DOI: 10.1111/ane.12481
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for glioblastoma patients - a clinical population-based study

Abstract: This population-based study supports the importance of surgery instead of biopsy only, followed by radiotherapy and chemotherapy, a finding which has also been stated in earlier non-population-based reports. However, it is obvious that the solution is not just surgical radicality followed by optimal oncological treatment. It is of great importance to seek further subclassifications, biomarkers, and new treatment modalities to make a significant change in survival for individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 30 publications
7
33
0
Order By: Relevance
“…Solely younger age in accordance with Combs et al 22 and Fekete et al 23 and smaller tumour volume in line with the results of Fogh et al 8 and Niranjan et al 24 remained significant as well-known crucial prognostic factors. Thus, it must be assumed that in this selected cohort, further still unknown favourable factors of influence are yet to be discovered.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Solely younger age in accordance with Combs et al 22 and Fekete et al 23 and smaller tumour volume in line with the results of Fogh et al 8 and Niranjan et al 24 remained significant as well-known crucial prognostic factors. Thus, it must be assumed that in this selected cohort, further still unknown favourable factors of influence are yet to be discovered.…”
Section: Discussionsupporting
confidence: 84%
“…Solely younger age in accordance with Combs et al 22 and Fekete et al 23 To develop hypotheses about prognostic factors in this positively selected cohort, we defined a subgroup of four patients as long-term survivors. In this "re-selection," well-known positive prognostic factors such as methylated MGMT promoter, initial complete tumour resection, adjuvant treatment with temozolomide, finalization of initial maintenance chemotherapy and small tumour volumes at recurrence were found predominantly.…”
Section: Discussionmentioning
confidence: 99%
“…The survival of GBM patients is related to multiple factors, where age, performance status, multiple lesions, resection status are independent prognostic factors as well as time from initial presentation to surgery …”
Section: Introductionmentioning
confidence: 99%
“…Standard treatment‐surgery followed by temozolomide chemotherapy with concomitant radiotherapy‐does not have “curative” intent but rather aims at preventing disease recurrence and extending survival while preserving patients' quality of life . Research has shown that younger age, better performance status, unifocal tumor location, degree of surgical resection, any surgical resection as opposed to biopsy only, and postsurgical treatment (radiotherapy/chemotherapy) are among the most important prognostic factors of survival after diagnosis . Moreover, O6‐methylguanine‐DNA methyltransferase (MGMT) promotor methylation, which is believed to predict response to chemotherapy, is reportedly predictive of longer survival after diagnosis of a GBM …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Research has shown that younger age, better performance status, unifocal tumor location, degree of surgical resection, any surgical resection as opposed to biopsy only, and postsurgical treatment (radiotherapy/chemotherapy) are among the most important prognostic factors of survival after diagnosis. [5][6][7] Moreover, O6methylguanine-DNA methyltransferase (MGMT) promotor methylation, which is believed to predict response to chemotherapy, 8 is reportedly predictive of longer survival after diagnosis of a GBM. 9,10 The disease-specific symptom burden that accompanies GBM often includes highly debilitating sequelae such as paresis, sensory loss, visual-perceptual deficits, cognitive deficits, and seizures.…”
Section: Introductionmentioning
confidence: 99%